أهمية الاندماج والاستحواذ كتوجه حديث لتعزيز الاداء المالي والتنافسي للمصارف المحلية الفلسطينية (دراسة حالة بنك فلسطين والبنك الوطني) - وصفي عوض, عزمي (Université de M'Sila, 2019)
هدفت الدراسة إلى التعرف على ماهية ودوافع الاندماج والاستحواذ المصرفي كتوجه حديث في القطاع المصرفي الفلسطيني ، وتقييم عمليات الاندماج والاستحواذ التي اجرتها البنوك الوطنية الفلسطينية وتأثيرها في تعزيز الاداء المالي والتنافسي للبنوك المدمجة ، وقد خلصت الدراسة الى العديد من النتائج أهمها أن القرارات الصادرة عن سلطة النقد الفلسطينية والخاصة برفع الحد الادنى لرأس مال البنوك العاملة في فلسطين كان له الأثر الايجابي في تكوين وحدات مصرفية وطنية قادرة على المنافسة والمشاركة بفاعلية تجاه تمويل خطط التنمية الاقتصادية . وبناء على نتائج الدراسة فإن الباحث أوصى بضرورة ان تقوم السلطات النقدية بتقديم حوافز اضافية لتشجيع عمليات الدمج والاستحواذ للقيام بدور اكثر فاعليه تجاه تمويل اقامة المشاريع الانتاجية ، وبإجراء تقييم دوري لأداء البنوك الفلسطينية للخروج بتوصيات تصب في المحصلة النهائية بمصلحة تطوير وتعزيز منظومة القطاع المصرفي الفلسطيني لمواجهة التحديات التنافسية والأزمات الماليه . The study aimed to identify the nature and motives of bank mergers and acquisitions as a modern trend in the Palestinian banking sector, And the evaluation of the mergers and acquisitions carried out by the Palestinian national banks and their impact on enhancing the financial and competitive performance of the merged banks, The study concluded that the decisions issued by the Palestinian Monetary Authority concerning raising the minimum capital of the banks operating in Palestine had a positive impact on the formation of national banking units capable of competing and participating effectively in financing economic development plans, Based on the results of the study,the researcher recommended that the Monetary Authority provide additional incentives to encourage mergers and acquisitions in the Palestinian banking sector to play a more active role towards financing the establishment of productive projects, And a periodic evaluation of the performance of banks operating in Palestine to come out with recommendations in the final outcome of the interest of developing and strengthening the Palestinian banking to meet the competitive challenges and financial crises. Keywords: Mergers and Acquisitions, Financial and Competitive Performance, Local Banks .
Keywords: الاندماج والاستحواذ ، الاداء المالي ، الاداء التنافسي ، المصارف المحلية